Motherhood and Tenure: Can Catholic Universities Support Both? - Ravizza, Bridget Burke; Peterson-Iyer, Karen (Catholic Education: A Journal of Inquiry and Practice, 2005)
This paper presents a plan for the implementation of more family-friendly policies at Catholic colleges and universities, both as a matter of justice for women and on behalf of the well being of families. It is motivated by the teachings of the Catholic social tradition that emphasize the equality and dignity of women; the importance of the dual vocations of Christian parents, who are called to raise children and to work more publicly on behalf of the common good; and the inherent value of children and their right to be properly nutured and educated within the Christian family. Our starting point is the condition of families in the U.S. today as they struggle to thrive in spite of tremendous demands placed on parents who also work outside the home. We examine the negative effects on women and families that result from a refusal to accommodate parents with young children in the workplace. We are concerned in particular with the challenges faced by women academics at colleges and universities who are also mothers. We argue that, by and large, these women are not adequately supported in academia, even at Catholic universities, in spite of that tradition’s professed commitment to the health and well being of families. Finally we offer several concrete suggestions by which universities may better support women academics who are mothers, thereby contributing to the well being of women and families.